2021
DOI: 10.1187/cbe.21-04-0106
|View full text |Cite
|
Sign up to set email alerts
|

Enthusiastic but Inconsistent: Graduate Teaching Assistants’ Perceptions of Their Role in the CURE Classroom

Abstract: Expectancy-value theory was used to explore how graduate teaching assistants (GTAs) value for teaching a course-based undergraduate research experience (CURE) impacts their motivation and perceptions of their role as CURE mentors. GTAs have varying perceptions of their role that do not closely correspond to their value for teaching CUREs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Fewer studies focus on variation in GTA behavior when teaching lab sections of the same course [ 27 , 29 , 65 ]. Our own interview analysis with the GTAs participating in this study indicates that GTAs teaching the same CURE can have vastly different conceptions of their instructor role, which likely influences the instructional decisions made by GTAs [ 27 ]. We expect that some of the variation that students perceive about what is most or least prioritized in the classroom ( Fig 2B , Fig 2C ) is a direct reflection of the effort GTAs put toward providing students with those experiences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fewer studies focus on variation in GTA behavior when teaching lab sections of the same course [ 27 , 29 , 65 ]. Our own interview analysis with the GTAs participating in this study indicates that GTAs teaching the same CURE can have vastly different conceptions of their instructor role, which likely influences the instructional decisions made by GTAs [ 27 ]. We expect that some of the variation that students perceive about what is most or least prioritized in the classroom ( Fig 2B , Fig 2C ) is a direct reflection of the effort GTAs put toward providing students with those experiences.…”
Section: Discussionmentioning
confidence: 99%
“…GTAs who explained the pedagogical rationale for implementing a CURE, as well as the potential benefits to students from participating in a CURE, may have contributed to students’ beliefs that they were participating in the CURE for student-centered purposes. In interviews conducted with the nine GTAs involved in our study (presented in [ 27 ]), we observed that a couple of the GTAs doubted the value for students of participating in a CURE, particularly at an introductory level. While documentation of instructor talk was beyond the scope of this study, it is possible that these GTAs may have actively engaged in unproductive instructor talk, such as expressing their doubt about the pedagogical advantages of the curriculum to their students [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations